The impact of cardiovascular disease on all-cause and cancer mortality: results from a 16-year follow-up of a German breast cancer case-control study - Möhl, Annika; Behrens, Sabine; Flaßkamp, Fabian; Obi, Nadia; Kreienbrinck, Annika; Holleczek, Bernd; Gali, Kathleen; Chang-Claude, Jenny; Becher, Heiko (Breast cancer research, 2023)
Background: Cardiovascular disease (CVD) is the leading cause of death worldwide. The aim of this study was to examine if CVD affects the mortality of women after a breast cancer diagnosis and population controls differently. Methods: The analysis included a total of 3,555 women, diagnosed with primary stage 1–3 breast cancer or in situ carcinoma between 2002 and 2005 and 7,334 controls breast cancer-free at recruitment, all aged 50–74 years, who were followed-up in a German breast cancer case–control study until June, 30 2020. Kaplan–Meier and cumulative incidence function were calculated for all-cause mortality and mortality from any cancer, stratified for case–control status and CVD, separately for women aged < 65 and ≥ 65 years. Cox regression and Fine-Gray subdistribution hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (95% CI) for the association between case–control-status, CVD and mortality from all causes/any cancer. Results: The median follow-up was 16.1 years. In total, 1,172 cases (33.0%) and 1,401 initial controls (19.1%) died. CVD prevalence at recruitment was 15.2% in cases and controls. Cases with CVD had the highest and controls without CVD the lowest mortality during the entire observation period in both age groups (< 65 and ≥ 65 years). CVD was identified as a risk factor for all-cause mortality in both cases and controls aged < 65 years (HR 1.22, 95%CI 0.96–1.55 and HR 1.79, 95%CI 1.43–2.24) as well as at ages of ≥ 65 years (HR 1.44, 95%CI 1.20–1.73 and HR 1.59, 95%CI 1.37–1.83). A significant association of CVD and cancer mortality was found only for cases aged ≥ 65 years. Conclusion: CVD was significantly associated with all-cause mortality of both cases and controls and CVD was identified as a risk factor for cancer mortality of cases aged ≥ 65 years at recruitment. Therefore, attention should be paid on monitoring and preventing CVD in breast cancer patients, especially in those diagnosed at older ages.
Veröffentlicht: 27. Juli 2023
Gesehen am 28.08.2023